RoleModelVis: A Visualization of Logical Story Models - Chen, Sherol; Deunsing, Andrew; Kong, Peter; Jhala, Arnav; Wardrip-Fruin, Noah; Mateas, Michael (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
In this demo we present a visualization of formalized representations of story. Introducing the interactive to storytelling requires the management of experiences that a user creates by their decisions. These sorts of variations can have impact on not only the user, but also the retrievable content appropriate to present to the user. The overall contribution of this work is to identify the player impact of story variation by modeling supplementary variations, and systematically responding to player interaction through supplementary variation, while respecting the author’s intentions by maintaining the integrity of the core story skeleton.